Aerosol-assisted chemical vapor deposition of nickel sulfide nanowires for electrochemical water oxidation. (30th December 2022) - Ehsan, Muhammad Ali; Khan, Abuzar; Zafar, Muhammad Nadeem; Akber, Usman Ali; Hakeem, Abbas Saeed; Nazar, Muhammad Faizan
Abstract: Slow kinetics and emotive design of electrocatalysts are the main barriers to effective oxygen evolution and hydrogen production from water. To overcome these challenges, nickel sulfide impregnated electrocatalysts with auxiliary structural features have recently attracted attention as effective alternatives for the oxygen evolution reaction (OER). Herein, nickel sulfide (NiS) nanowires are developed directly on nickel foam (NF), which have proven to be a highly efficient electrocatalyst for OER in an alkaline medium. For this, NiS nanowires were grown on NF for short intervals of 30, 60, 90 and 120 min through an aerosol-assisted chemical vapor deposition (AACVD) process using nickel diethyldithiocarbamate as a precursor. The as-developed NiS electrode showed excellent OER activity in 1.0 M KOH solution. It is noteworthy that the NiS electrode produced after 90 min provides a reference current density of 10 mA cm −2 at an overpotential (η) of 210 mV and achieves a higher current density of 500 mA cm −2 at an overpotential of 340 mV. Moreover, the nanocatalyst has observed a low Tafel value (60 mV dec −1 ) and good OER stability. After the electrolysis, it was found that the surface of the NiS catalyst was partially modified into nickel oxide. The S atom in the NiS catalyst can provide an activator function that first converts the sulfide to a hydroxide and then eventually becomes an oxyhydroxide species. The more active nickel hydroxide/oxyhydroxide phase raises the water oxidation performance to a new level. The facile synthesis of NiS nanowire films by AACVD tends to be used as an anodic material in various other power generation and energy conversion devices such as batteries, fuel cells, and supercapacitors. Graphical abstract: Image 1 Highlights: Time dependent fabrication of NiS via aerosol assisted chemical vapor deposition. NiS-90 min variant exhibited remarkable oxygen evolution reaction (OER) activity. Partial transformation NiS into more active NiO was responsible for efficient OER.